FAKTOR-FAKTOR YANG MEMENGARUHI KESADARAN MORAL DAN KEMUNAFIKAN - Irfan Fahmi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
Literature study identify two religion practices suspected affecting moral awareness ; praying before doing activity and cleansing before praying. Factorial 2x2 experimental study was used to analyse hypothesis. Participants are 103 students from psychology faculty UIN Sunan Gunung Djati Bandung taking intelegency test class. Result shows that praying before doing activity and cleansing before praying for physical purity are not significantly proven affecting moral awareness and moral behavior since cheating and liar are still occured. One factor which is significantly proven affect moral behavior is moral belief.